PENGARUH JOB SATISFACTION DAN WORK LIFE BALANCE TERHADAP TURNOVER INTENTION - Anisa Fajriah; Sri Ekowati; Dedy Wahyudi (UM. Bengkulu, 2026)
This study aims to determine the effect of job satisfaction and work-life balance on turnover intention among employees of PT Wahana Semesta Bengkulu Television. This study used a quantitative method with a sample of 55 respondents using a total sampling technique. Data collection techniques used a questionnaire. Data analysis techniques used multiple linear regression analysis, coefficient of determination (R2) analysis, and hypothesis testing. The results showed that job satisfaction did not have a positive and significant effect on turnover intention (Y) among employees of PT Wahana Semesta Bengkulu Television. The lower the level of employee satisfaction with their work, the more likely they were to leave the company. Work-life balance did not have a positive and significant effect on turnover intention (Y) among employees of PT Wahana Semesta Bengkulu Television. This means that when employees perceive a greater balance between their work and life, they are more likely to consider leaving the company. Job satisfaction (X1) and work-life balance (X2) had a positive and significant effect on turnover intention (Y) among employees of PT Wahana Semesta Bengkulu Television. This means that the more satisfied employees are with their jobs and have a better work-life balance, the more likely they are to leave the company. This is a step towards a good relationship. Keywords: Job Satisfaction, Work Life Balance, Turnover Intention